Pioneers of Science and Discovery: William Hawey and the Circulation of the Blood - Neil, Eric (Priory Press Ltd, 1975)
The author wrote this book in a simple and exciting way and gives a valuable insight into how scientific theories develop. He sets out the modern view of the circulation and then takes the story of the heart and blood system through from the Greeks to Harvey and beyond...
Keywords: Science - Blood Circulation; Non-Fiction